Implementation of Qiroatul Kutub in Student Character Building at MA Matholi'ul Huda Bugel Jepara - Muhammad Yusuf Asy'ari; Alex Yusron Al Mufti (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2025)
This study aims to obtain the results of Qiroatul Kutub learning as a tool for developing student character at MA Matholi'ul Huda Bugel Kedung Jepara. This study involved 33 grade 10 students and several teachers as respondents. This study uses descriptive qualitative analysis, observation, interviews and quantitative calculations to determine how much influence the implementation has. The findings of this study indicate that Qiroatul Kutub tends to be very influential in instilling character values in students. These results are presented with 54.55% of all student respondents. However, in its implementation, it still faces several challenges, including differences in the level of student understanding and the lack of a dynamic learning model to make it easier for students to understand the lesson.